Study on the calculation method of electrical quantity for connection line open-phase operation of wind farm connected to MMC-HVDC Considering negative sequence current suppression - Botong Li; Yuejin Dong; Xinru Jiao; Xiaolong Chen; Bin Li; Liang Ji (International Journal of Electrical Power & Energy Systems, 2024)
The open-phase operation of the AC connection line connecting the wind farm and MMC generates negative sequence current in the system, which cause the overcurrent, overvoltage, power fluctuation and other problems. It seriously affects the power transmission and equipment safety. Therefore, it is of great significance to study the negative sequence current suppression scheme suitable for the open-phase operation and master the calculation method of electrical quantities for improving the utilization rate of wind power and ensuring the stability of the system. Based on the negative sequence current relationship between wind farm and MMC, coordinated control schemes to suppress the negative sequence current by wind farm or MMC are proposed. The calculation method of the electrical quantities for two negative sequence current suppression schemes are studied, and their requirements on the voltage and current resistance for equipment of wind farm and MMC are calculated respectively. The accuracy of the calculation method is verified in PSCAD/EMTDC, and it gives the quantitative requirements of the negative sequence control scheme on the tolerance of the system in the specific example.